Tablet Shrouding Process Optimization with the Addition of Extended Fin to Improve Product Quality and Production Efficiency - Riyanto, Agus; Akbar, Ali (Indonesian Journal of Microbiology, 2024)
In general, tablets are solid dose forms containing therapeutic substances, with or without fillers. Tablet compression is achieved by applying high pressure on powder (bulk) granules through a steel mold. The core tablet to be coated must meet certain standards because it will be moved and slammed repeatedly throughout the coating process. The extended fin is an additional fin that functions when the product is inserted into the coating pan and rotated, preventing the product from coming into direct contact with the coating pan wall during the coating process, resulting in friction and reactions that occur during the film coating process. For this reason, an expanded fin is inserted to reduce friction between the product and the pan coating machine's wall. The addition of the extended fin decreases friction between the drug and the machine wall, preventing the product coating process from reacting due to excessive friction with the machine wall. Additionally, the results of smoothness, glossiness, and color solidity are excellent. This resolves the issues that have previously lowered the proportion of production output.